Review of the Formulation of the Professional Certification Scheme - Agus Sutarna; Efri Syamsul Bahri; Suyadi Murdi Wiharjo; Mohd Mizan Mohammad Aslam (Sultan Publisher, 2023)
Certification schemes in Indonesia have become an essential issue in this decade. This research describes how to formulate a Professional Certification Scheme in Indonesia. This study uses a qualitative method. The research approach was carried out in a descriptive and literature study. Data comes from regulations and reference journal articles. The data were analyzed descriptively to explain how the Certification Scheme was formulated. The results of this study found that the formulation of the Certification scheme in Indonesia refers to the Regulation of the National Professional Certification Agency Number: 2/BNSP/VIII/2017. A Professional Certification Scheme can be formulated based on the KKNI (Qualification Level), Occupation/Occupation, and Cluster (group). The preparation of the Professional Certification Scheme document refers to Format A as stated in the National Professional Certification Agency Regulation Number: 2/BNSP/VIII/2017. The government must allocate resources to produce various formulations of Professional Certification Schemes required by Indonesian employment stakeholders.